Preparation of a monodisperse nano-titanium dioxide@cuprous oxide heterojunction catalyst dispersion
By combining titanium dioxide with cuprous oxide to form nanotitanium dioxide@crystalline oxide heterojunction catalyst, the problem of low solar light utilization and charge separation efficiency of titanium dioxide photocatalysts is solved, and the catalyst efficiency is achieved through the liquid phase dispersion form Recycling and reuse improves catalytic performance and application convenience.
Patent Information
- Application Number
- CN202211497144.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-24
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-11-24
AI Technical Summary
The existing titanium dioxide photocatalysts have a wide band gap and a short photogenerated charge life generated by photoexcitation, which leads to low solar light utilization and low charge separation efficiency, and it is difficult to recover and reuse powder catalysts in practical applications.
Combining titanium dioxide with cuprous oxide to form a nano-titanium dioxide@crystalline cuprous oxide heterojunction catalyst. A liquid phase dispersion with small particle size and uniform particle size was prepared by solvothermal method to broaden the light absorption range, improve the charge separation efficiency, and pass Supported on the support to achieve direct recovery and reuse of the catalyst.
The solar light utilization rate and photocatalytic rate are improved, efficient recovery and reuse of catalysts are achieved, and the stability and application convenience of catalysts are enhanced.
Smart Images

Figure HDA0003960746190000011 
Figure HDA0003960746190000012 
Figure HDA0003960746190000013
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano photocatalysis technology; more specifically, to a method for preparing a monodispersed nano titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion. Background Art
[0002] Hydrogen energy is considered to be a promising secondary energy source due to its advantages such as cleanness, high calorific value, easy storage and transportation, and high conversion rate. The conversion of water into hydrogen energy by photocatalytic decomposition of solar energy is an effective way to solve global environmental pollution and energy crisis at the same time. The key to the reaction of photocatalytic decomposition of water to produce hydrogen lies in the selection of catalysts. So far, many researchers have explored materials that can be used as photocatalysts. Titanium dioxide has become one of the most popular photocatalysts because of its excellent photocatalytic activity and good chemical stability, and its long-term benefit to the ecological and natural environment. However, titanium dioxide itself also has shortcomings. First, its band gap is wide and can only be excited by ultraviolet rays, resulting in only 5% of sunlight being utilized, with low utilization rate; and the photogenerated charge generated by photoexcitation has a short life span, and photogenerated electrons and holes are very easy to recombine, resulting in low charge separation efficiency. In addition, most of the common catalysts are in powder form. In the actual application process, filtration and centrifugation are required to separate the catalyst. The process is cumbersome and makes it difficult to recycle and reuse the catalyst. Summary of the invention
[0003] First, in order to solve the problems of low utilization rate of sunlight and low efficiency of charge separation, titanium dioxide and cuprous oxide are compounded to improve the valence band position, narrow the bandgap width, and then broaden the light absorption range and improve the utilization rate of sunlight; and a heterojunction is formed between the p-type semiconductor titanium dioxide and the n-type semiconductor cuprous oxide, which generates a built-in electric field, accelerates the separation of photogenerated electrons and holes, improves the separation efficiency, and then improves the photocatalytic rate. Secondly, the present invention prepares a monodisperse nano titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion, which is more advantageous than the catalyst in the common powder state, has a small particle size, uniform particle size distribution, many active sites, good dispersibility in the liquid phase medium, and can be evenly and firmly loaded on nylon, carbon cloth, carbon paper, FTO, ITO, quartz glass, glass, foam nickel, aerogel and other carriers for use, which is conducive to the direct recovery and reuse of the catalyst, clean and environmentally friendly.
[0004] The invention mainly adopts a solvent thermal preparation process to prepare a monodisperse nano titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion with small particle size and uniform particle size distribution. The nano titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion of the invention has a solid content of 0.01-60wt.%, and a single dispersion is a nanorod on which dispersed cuprous oxide nanoparticles are uniformly grown. The particle size of cuprous oxide is 1-2nm, and the cuprous oxide nanoparticles grow on the titanium dioxide nanorod in a coherent growth manner, and a heterojunction interface is formed at the connection.
[0005] A method for preparing a monodisperse nano-titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion, characterized in that it comprises the following steps:
[0006] 1) using alcohol as solvent, adding a titanium salt precursor and a hydrolysis accelerator thereto to prepare a titanium salt solution;
[0007] 2) using alcohol as solvent and adding water thereto to prepare a hydrolyzate;
[0008] 3) mixing the titanium salt solution in step 1) and the hydrolyzate in step 2) to react to obtain a reaction solution A;
[0009] 4) transferring the reaction solution A to a high temperature and high pressure reactor for solvothermal reaction to obtain a white precipitate of titanium dioxide;
[0010] 5) washing and modifying the titanium dioxide white precipitate, and then dispersing it in different solvents to obtain a monodisperse anatase nano-titanium dioxide transparent liquid phase dispersion;
[0011] 6) using water, an organic solvent or a mixture of water and an organic solvent as a solvent, adding a copper salt precursor thereto to prepare a copper salt precursor solution;
[0012] 7) using water, an organic solvent or a mixture of water and an organic solvent as a solvent, adding a surface modifier thereto to prepare a surface modifier solution;
[0013] 8) mixing the monodisperse anatase nano-titanium dioxide transparent liquid dispersion with the copper salt precursor solution and the surface modifier solution to obtain a reaction solution B, and subjecting the solution to solvent thermal treatment to obtain a titanium dioxide@copper oxide precipitate;
[0014] 9) washing the titanium dioxide @ copper oxide precipitate, and then dispersing it in different solvents to obtain a monodisperse nano titanium dioxide @ copper oxide liquid phase dispersion;
[0015] 10) Adding an oxidant into the monodisperse nano-titanium dioxide@copper oxide liquid phase dispersion to prepare a monodisperse nano-titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion.
[0016] In step 1), the titanium salt precursor is selected from one or more of the following substances: butyl titanate, isopropyl titanate, titanium tetrachloride, titanium sulfate, and titanyl sulfate.
[0017] In step 1), the hydrolysis promoter is selected from one or more of the following substances (acids and bases are not mixed, that is, acids and bases are not used at the same time): potassium hydroxide, sodium hydroxide, ammonia water, triethanolamine, ethylenediamine, triethylamine, n-propylamine, tert-butylamine, tripentylamine, decylamine, dodecylamine, trilaurylamine, oleylamine, octadecylamine, ammonium carbonate, ammonium bicarbonate, formic acid, acetic acid, n-butyric acid, phosphoric acid, oxalic acid, hydrochloric acid, sulfuric acid, nitric acid, glycine, lysine, and ethylenediaminetetraacetic acid.
[0018] In step 1) and step 2), the alcohol solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, n-butanol, n-hexanol, n-octanol, n-decanol, isopropanol, isobutanol, isopentanol, ethylene glycol, diethylene glycol, glycerol, and 1,2-butanediol.
[0019] In step 1), the concentration of the titanium salt precursor solution is 1-50wt.%, and the concentration of the hydrolysis promoter solution is 0.5-30wt.%; preferably, the concentration of the titanium salt precursor solution is 10-50wt.%, and the concentration of the hydrolysis promoter solution is 1-20wt.%.
[0020] In step 2), the volume ratio of alcohol to deionized water in the hydrolyzate is 20-60:1-50.
[0021] In step 3), the titanium salt and the hydrolyzate are mixed in the following manner: the titanium salt solution and the hydrolyzate are placed in storage tanks respectively, preheated to the reaction temperature, and then added to the reactor for reaction; the adding process temperature is 0 to 65°C; the adding method is simultaneous addition, the titanium salt solution is added to the hydrolyzate, or the hydrolyzate is added to the titanium salt solution.
[0022] Preferably, the reactor comprises a tank reactor, a high gravity rotating packed bed reactor, a stator-rotor reactor, a microchannel reactor or a static mixing reactor.
[0023] In step 4), the solvent thermal temperature is 80 to 240° C. and the time is 6 to 120 hours.
[0024] In step 5), the modification is to add a modifier to the washed titanium dioxide, and the mass fraction of the modifier to the titanium dioxide is 0.05-800wt.%; the modifier used in the modification is selected from one or more of the following substances: polyethylene glycol 400, polyethylene glycol 2000, polyethylene glycol 8000, polyvinyl alcohol, polyvinyl pyrrolidone, silane coupling agent KH792, silane coupling agent KH570, silane coupling agent KH550, silane coupling agent KH560, decanoic acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, oleic acid, oleylamine, dodecylamine, hexadecylamine, octadecylamine, hexadecyltrimethylammonium bromide, sodium oleate, sodium dodecylbenzenesulfonate, sodium petroleum sulfonate, sodium stearate, sodium dodecyl sulfate.
[0025] In step 5), the solvent is selected from one or more of the following substances: water, methanol, ethanol, ethylene glycol, glycerol, n-propanol, isopropanol, n-butanol, 1,2-butanediol, benzyl alcohol, anisole, ethyl acetate, butyl acetate, toluene, tetrahydrofuran, dichloromethane, chloroform, tetrachloromethane, cyclohexane, n-hexane, n-heptane, petroleum ether (30-60° C.), petroleum ether (60-90° C.), kerosene, naphtha, white oil, fish oil, castor oil, peanut oil, methyl isobutyl ketone, propylene glycol methyl ether, propylene glycol methyl ether acetate, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and pyridine.
[0026] In step 5), the dispersion method is mechanical stirring, magnetic stirring, homogenizer dispersion, three-roller dispersion or ultrasonic dispersion.
[0027] In step 6), the copper salt precursor is selected from one or more of the following substances: anhydrous copper sulfate, copper sulfate monohydrate, copper sulfate pentahydrate, copper nitrate trihydrate, copper chloride dihydrate, anhydrous copper chloride, copper acetylacetonate, and copper hydroxide.
[0028] In step 6), the organic solvent is selected from one or more of the following substances: methanol, ethanol, ethylene glycol, diethylene glycol, propylene glycol, glycerol, n-propanol, isopropanol, n-butanol, 1,2-butanediol, isobutanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, aniline, dimethyl sulfoxide, tetrahydrofuran, benzene, toluene, benzyl alcohol, anisole, xylene, cyclohexane, n-hexane, pyridine, methyl acetate, ethyl acetate, and butyl acetate.
[0029] In step 6), the concentration of the copper salt precursor solution is 0.5-50 wt. %; preferably, the concentration of the copper salt precursor solution is 0.5-20 wt. %.
[0030] In step 7), the surface modifier is selected from one or more of the following substances: polyethylene glycol 400, polyethylene glycol 2000, polyethylene glycol 8000, polyvinyl alcohol, polyvinyl pyrrolidone, silane coupling agent KH792, silane coupling agent KH570, silane coupling agent KH550, silane coupling agent KH560, butyric acid, decanoic acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, linoleic acid, oleic acid, oleylamine, dodecylamine, hexadecylamine, octadecylamine, hexadecyltrimethylammonium bromide, octadecene, sodium oleate, sodium dodecylbenzenesulfonate, sodium petroleum sulfonate, sodium stearate, sodium dodecyl sulfate;
[0031] Preferably, in step 7), the concentration of the surface modifier is 10 to 95 wt. %; more preferably, in step 7), the concentration of the surface modifier is 10 to 80 wt. %.
[0032] In step 8), the solvent thermal reaction temperature is 150-240° C., and the hydrothermal reaction time is 2-120 h.
[0033] In step 8), the concentration of the monodisperse anatase nano-titanium dioxide is 1-60wt.%; the volume ratio of the monodisperse anatase nano-titanium dioxide dispersion to the copper salt precursor solution and the surface modifier solution is 1-30:30-100:10-40.
[0034] In step 9), the solvent is selected from one or more of the following substances: water, methanol, ethanol, ethylene glycol, glycerol, n-propanol, isopropanol, n-butanol, 1,2-butanediol, benzyl alcohol, toluene, anisole, tetrahydrofuran, ethyl acetate, butyl acetate, dichloromethane, chloroform, tetrachloromethane, cyclohexane, n-hexane, n-heptane, petroleum ether (30-60° C.), petroleum ether (60-90° C.), pyridine, kerosene, naphtha, white oil, fish oil, castor oil, peanut oil, methyl isobutyl ketone, propylene glycol methyl ether, propylene glycol methyl ether acetate, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide;
[0035] Preferably, in step 9), the dispersion method is mechanical stirring, magnetic stirring, homogenizer dispersion, three-roller dispersion or ultrasonic dispersion.
[0036] In step 10), the oxidant includes one or more of a gaseous oxidant, a liquid oxidant, and a solid oxidant;
[0037] Preferably, the gaseous oxidant is selected from one or more of the following substances: air, compressed air, oxygen, ozone; the addition method is to directly introduce it into the liquid of the monodisperse nano-titanium dioxide@copper oxide liquid phase dispersion in step 9); the introduction rate is 0 to 150 L / h (the introduction rate is 0, that is, directly exposed to the gaseous oxidant);
[0038] Preferably, the liquid oxidant is selected from one or more of the following substances: hydrogen peroxide solution, nitric acid, concentrated sulfuric acid; the solid oxidant is selected from one or more of the following substances: potassium permanganate, ammonium persulfate, sodium perborate, potassium perborate;
[0039] The liquid and solid oxidants are added directly or mixed with a solvent before being added to the reaction solution; the solvent used is water, an organic solvent, a mixture of an organic solvent and water, or a mixture of different organic solvents; the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, tetrahydrofuran, toluene, cyclohexane, n-hexane, n-heptane, dichloromethane, chloroform, carbon tetrachloride, ethyl acetate, butyl acetate, dimethyl sulfoxide, castor oil, white oil, naphtha, diesel, triethylamine, triethanolamine, formic acid, acetic acid, n-butyric acid; the concentration is 0.5-50wt.%.
[0040] The prepared monodisperse nano-titanium dioxide@cuprous oxide liquid phase dispersion is loaded on a carrier such as nylon, carbon cloth, carbon paper, FTO, ITO, quartz glass, glass, nickel foam, aerogel, etc. by spin coating, scraping, spraying or dipping and pulling, and then placed in a reactor filled with water, and then 1-20 vol.% methanol solution is added as a sacrificial agent, and a xenon lamp with a power of 300 W is used for illumination, and the wavelength range of the light source is 200-1000 nm to carry out photocatalytic hydrogen production.
[0041] 1. The length of the titanium dioxide nanorods prepared by the present invention is 30 to 60 nm, and the diameter of the cuprous oxide particles is 1 to 2 nm. The small particle size can increase the active sites of the redox reaction, thereby improving the hydrogen production rate;
[0042] 2. Combine titanium dioxide and cuprous oxide together through a solvothermal method, so that cuprous oxide is distributed on the surface of titanium dioxide, increasing the absorption range of sunlight and forming a coherently grown heterojunction interface, which can effectively improve the charge separation efficiency;
[0043] 3. The catalyst is dispersed in an organic solvent with uniform particle size, and can be firmly loaded on some carriers, which is conducive to the recovery and reuse of the catalyst.
[0044] 4. Making the catalyst into a monodisperse liquid phase dispersion is a highlight of this patent, which can achieve a firm load on the carrier; BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 Schematic diagram of the reaction of the catalyst prepared by the present invention.
[0046] Figure 2This is a transmission electron microscope photo of the nano-titanium dioxide@cuprous oxide heterojunction catalyst prepared by the present invention.
[0047] Figure 3 This is a test diagram of the hydrogen production performance of Example 1 of the present invention. DETAILED DESCRIPTION
[0048] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0049] Example 1
[0050] A method for preparing a monodisperse titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion, comprising the following steps:
[0051] 1) Prepare titanium salt solution: mix 80 mL of ethanol, 40 mL of butyl titanate, and 4 mL of triethanolamine and stir magnetically for 30 min;
[0052] 2) Prepare hydrolyzate: Mix 40 mL of ethanol and 8 mL of deionized water;
[0053] 3) placing the titanium salt solution in a tank reactor, adding the hydrolyzate dropwise into the titanium salt solution, controlling the reaction temperature to 40° C. and the stirring rate to 500 r / min, to obtain a reaction solution A;
[0054] 4) Transfer the reaction solution A to a high temperature and high pressure reactor and heat at 130°C for 96 hours to obtain a white precipitate of titanium dioxide;
[0055] 5) 9.4 g of titanium dioxide white precipitate was centrifuged, washed with anhydrous ethanol 4 times, and 920 mg of stearic acid was added as a modifier, and then dispersed in 100 mL of toluene to obtain a monodisperse anatase nano-titanium dioxide transparent liquid phase dispersion;
[0056] 6) Prepare a copper salt precursor solution: dissolve 2.50 g of cupric chloride dihydrate in a mixture of 50 mL of ethanol and 50 mL of deionized water;
[0057] 7) dissolving 5.40 g of myristic acid in 25 mL of ethanol to prepare a surface modifier solution;
[0058] 8) The titanium dioxide transparent liquid dispersion of step 5) and the surface modifier solution of step 7) are completely mixed, and added dropwise to the copper salt precursor solution of step 6), and the reaction temperature is controlled to be 40° C. and the magnetic stirring rate is 500 r / min to obtain reaction solution B; the reaction solution B is transferred to a high temperature and high pressure reactor and subjected to solvent heating at 180° C. for 60 h to obtain titanium dioxide@copper oxide precipitate;
[0059] 9) The titanium dioxide @ copper oxide precipitate was centrifuged, washed with anhydrous ethanol for 4 times, and dispersed in 100 mL of toluene to obtain a monodisperse nano titanium dioxide @ copper oxide toluene phase dispersion;
[0060] 10) Dissolve 1 mL of concentrated nitric acid in 10 mL of methanol to prepare an oxidant solution, and add the oxidant solution to the nano-titanium dioxide@copper oxide toluene phase dispersion in step 9) for oxidation to prepare a monodisperse nano-titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion.
[0061] 11) The obtained nano heterojunction catalyst titanium dioxide nanorods have a length of 30 to 60 nm, the cuprous oxide particles have a diameter of 1 to 2 nm, the particles have a high specific surface area, the particles are evenly dispersed, the obtained nano dispersion does not settle for ≥6 months, and the dispersion remains transparent and stable.
[0062] Photocatalytic hydrogen production effect:
[0063] The prepared monodisperse nano-titanium dioxide@cuprous oxide liquid phase dispersion was loaded on a glass sheet (50mm*50mm*1mm) carrier by spin coating, and then placed in a reactor filled with water, and a 10vol.% methanol solution was added as a sacrificial agent. A 300W xenon lamp with an AM 1.5G filter was used as a simulated light source for sunlight. The relationship between the hydrogen production and the illumination time is shown in the figure. Figure 3 shown.
Claims
1. A method for preparing a monodisperse nano-titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion, characterized in that: The steps include: 1) Using alcohol as solvent, adding a titanium salt precursor and a hydrolysis accelerator thereto to prepare a titanium salt solution; 2) using alcohol as solvent and adding water thereto to prepare a hydrolyzate; 3) mixing the titanium salt solution in step 1) and the hydrolyzate in step 2) to react, to obtain a reaction solution A; 4) Transferring the reaction solution A to a high temperature and high pressure reactor for solvothermal reaction to obtain a white precipitate of titanium dioxide; 5) washing and modifying the titanium dioxide white precipitate, and then dispersing it in different solvents to obtain a monodisperse anatase nano-titanium dioxide transparent liquid phase dispersion; the modification is to add a modifier to the washed titanium dioxide, and the mass fraction of the modifier to the titanium dioxide is 0.05-800 wt.%; the modifier is myristic acid; 6) using an organic solvent or a mixture of water and an organic solvent as a solvent, adding a copper salt precursor thereto to prepare a copper salt precursor solution; 7) using water, an organic solvent or a mixture of water and an organic solvent as a solvent, adding a surface modifier thereto to prepare a surface modifier solution; the surface modifier is stearic acid; 8) mixing the monodisperse anatase nano-titanium dioxide transparent liquid dispersion with the copper salt precursor solution and the surface modifier solution to obtain a reaction solution B, and subjecting the solution to solvent thermal treatment to obtain a titanium dioxide@copper oxide precipitate; 9) washing the titanium dioxide @ copper oxide precipitate, and then dispersing it in different solvents to obtain a monodisperse nano titanium dioxide @ copper oxide liquid phase dispersion; 10) adding an oxidant to a monodisperse nano-titanium dioxide@copper oxide liquid phase dispersion to prepare a monodisperse nano-titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion; In step 6), the organic solvent is selected from one or more of the following substances: methanol, ethanol, ethylene glycol, diethylene glycol, propylene glycol, glycerol, n-propanol, isopropanol, n-butanol, 1,2-butanediol, isobutanol; In step 1), the titanium salt precursor is selected from one or more of the following substances: butyl titanate, titanium tetrachloride, titanium sulfate, and titanyl sulfate; In step 1), the hydrolysis promoter is selected from one or more of the following substances: potassium hydroxide, sodium hydroxide, ammonia water, triethanolamine, ethylenediamine, triethylamine, n-propylamine, tert-butylamine, tripentylamine, decylamine, dodecylamine, trilaurylamine, oleylamine, octadecylamine, ammonium carbonate, ammonium bicarbonate, formic acid, acetic acid, n-butyric acid, phosphoric acid, oxalic acid, hydrochloric acid, sulfuric acid, nitric acid, glycine, lysine, ethylenediaminetetraacetic acid, and the acid and the base are not mixed, that is, the acid and the base are not used at the same time; In step 1) and step 2), the alcohol solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, n-butanol, n-hexanol, n-octanol, n-decanol, isopropanol, isobutanol, isopentanol, ethylene glycol, diethylene glycol, glycerol, 1,2-butanediol; In step 1), the concentration of the titanium salt precursor solution is 1-50 wt.%, and the concentration of the hydrolysis accelerator solution is 0.5-30 wt.%; In step 2), the volume ratio of alcohol to deionized water in the hydrolyzate is 20-60: 1-50; In step 6), the copper salt precursor is selected from one or more of the following substances: anhydrous copper sulfate, copper sulfate monohydrate, copper sulfate pentahydrate, copper chloride dihydrate, anhydrous copper chloride, copper acetylacetonate; In step 6), the concentration of the copper salt precursor solution is 0.5-50 wt.%.
2. The method according to claim 1, characterized in that The concentration of the titanium salt precursor solution is 10-50 wt.%, and the concentration of the hydrolysis accelerator solution is 1-20 wt.%.
3. The method according to claim 1, characterized in that In step 3), the titanium salt and the hydrolyzate are mixed in the following manner: the titanium salt solution and the hydrolyzate are placed in storage tanks respectively, preheated to the reaction temperature, and then added to the reactor for reaction; the temperature of the adding process is 0-65° C.; the adding method is simultaneous addition, the titanium salt solution is added to the hydrolyzate, or the hydrolyzate is added to the titanium salt solution; The reactor includes a kettle reactor, a high gravity rotating packed bed reactor, a stator-rotor reactor, a microchannel reactor or a static mixing reactor; In step 4), the solvent thermal temperature is 80-240°C and the time is 6-120 h.
4. The method according to claim 1, characterized in that In step 5), the solvent is selected from one or more of the following substances: water, methanol, ethanol, ethylene glycol, glycerol, n-propanol, isopropanol, n-butanol, 1,2-butanediol, benzyl alcohol, anisole, ethyl acetate, butyl acetate, toluene, tetrahydrofuran, dichloromethane, chloroform, tetrachloromethane, cyclohexane, n-hexane, n-heptane, petroleum ether (30-60° C.), petroleum ether (60-90° C.), kerosene, naphtha, white oil, fish oil, castor oil, peanut oil, methyl isobutyl ketone, propylene glycol methyl ether, propylene glycol methyl ether acetate, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, pyridine; In step 5), the dispersion method is mechanical stirring, magnetic stirring, homogenizer dispersion, three-roller dispersion or ultrasonic dispersion.
5. The method according to claim 1, characterized in that In step 6), the concentration of the copper salt precursor solution is 0.5-20 wt.%.
6. The method according to claim 1, characterized in that In step 7), the concentration of the surface modifier is 10-95wt.%; In step 8), the solvent thermal reaction temperature is 150-240° C., and the hydrothermal reaction time is 2-120 h; In step 8), the concentration of the monodisperse anatase nano-titanium dioxide is 1-60 wt.%; the volume ratio of the monodisperse anatase nano-titanium dioxide dispersion to the copper salt precursor solution and the surface modifier solution is 1-30: 30-100: 10-40.
7. The method according to claim 6, characterized in that In step 7), the concentration of the surface modifier is 10-80 wt.%.
8. The method according to claim 1, characterized in that In step 9), the solvent is selected from one or more of the following substances: water, methanol, ethanol, ethylene glycol, glycerol, n-propanol, isopropanol, n-butanol, 1,2-butanediol, benzyl alcohol, toluene, anisole, tetrahydrofuran, ethyl acetate, butyl acetate, dichloromethane, chloroform, tetrachloromethane, cyclohexane, n-hexane, n-heptane, petroleum ether (30-60° C.), petroleum ether (60-90° C.), pyridine, kerosene, naphtha, white oil, fish oil, castor oil, peanut oil, methyl isobutyl ketone, propylene glycol methyl ether, propylene glycol methyl ether acetate, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide; In step 9), the dispersion method is mechanical stirring, magnetic stirring, homogenizer dispersion, three-roller dispersion or ultrasonic dispersion.
9. The method according to claim 1, characterized in that In step 10), the oxidant includes one or more of a gaseous oxidant, a liquid oxidant, and a solid oxidant; The gas oxidant is selected from one or more of the following substances: air, oxygen, ozone; the addition method is to directly introduce it into the liquid of the monodispersed nano-titanium dioxide@copper oxide liquid phase dispersion in step 9); the introduction rate is 0-150 L / h, and the introduction rate is 0, that is, directly exposed to the gas oxidant; The liquid oxidant is selected from one or more of the following substances: hydrogen peroxide solution, concentrated nitric acid, concentrated sulfuric acid; the solid oxidant is selected from one or more of the following substances: potassium permanganate, ammonium persulfate, sodium perborate, potassium perborate; The liquid and solid oxidants are added directly or mixed with a solvent before being added to the reaction solution; the solvent used is water, an organic solvent, a mixture of an organic solvent and water, or a mixture of different organic solvents; the organic solvent is selected from one or more of the following substances: methanol, ethanol, n-propanol, isopropanol, tetrahydrofuran, toluene, cyclohexane, n-hexane, n-heptane, dichloromethane, chloroform, carbon tetrachloride, ethyl acetate, butyl acetate, dimethyl sulfoxide, castor oil, white oil, naphtha, diesel, triethylamine, triethanolamine, formic acid, acetic acid, n-butyric acid; the concentration is 0.5-50 wt.%.
10. The monodispersed nano-titanium dioxide@cuprous oxide heterojunction catalyst liquid phase dispersion prepared by the method according to any one of claims 1 to 9, characterized in that: The solid content is 0.01-60 wt.%, and a single dispersion is a nanorod on which dispersed cuprous oxide nanoparticles are uniformly grown. The particle size of cuprous oxide is 1-2 nm. The cuprous oxide nanoparticles grow on the titanium dioxide nanorods in a coherent growth manner, and a heterojunction interface is formed at the connection.
11. Use of the monodisperse nano-titanium dioxide @ cuprous oxide heterojunction catalyst liquid phase dispersion prepared by the method according to any one of claims 1 to 9, wherein the prepared monodisperse nano-titanium dioxide @ cuprous oxide liquid phase dispersion is loaded on a nylon, carbon cloth, carbon paper, ITO, glass, nickel foam, or aerogel carrier by spin coating, blade coating, spray coating, or immersion pulling, and then placed in a reactor filled with water, and then 1 to 20 vol.% methanol solution is added as a sacrificial agent, and a xenon lamp with a power of 300 W is used for illumination, and the wavelength range of the light source is 200 to 1000 nm, and photocatalytic hydrogen production is performed.
12. The use according to claim 11, characterized in that The glass is selected from FTO and quartz glass.
Citation Information
Patent Citations
Preparation method and application of copper-porous titanium dioxide composite material with schottky junction structure
CN109225219A